Institutional investor monitoring motivation and the marginal value of cash - Ward, Charles; Yin, Chao; Zeng, Yeqin (Journal of Corporate Finance, 2018)
This paper examines whether the motivation of institutional investors in monitoring a firm is positively related to the relative importance of the firm's stock in their portfolios. We find that greater motivated monitoring institutional ownership is associated with a higher marginal value of corporate cash holdings, which cannot be explained by other corporate governance measures and institution types. Further, we find that the economic effect of institutional monitoring on the marginal value of cash falls with decreasing institutions' monitoring motivation. Based on these findings, we construct a monitoring motivation-weighted institutional ownership measure and document a positive relation between it and the marginal value of cash. Our results are robust after controlling for the endogeneity of institutional ownership, three cash regimes, firm size, and changes in US public firms over time.